2023
DOI: 10.1002/anie.202217171
|View full text |Cite
|
Sign up to set email alerts
|

The COVID19‐NMR Consortium: A Public Report on the Impact of this New Global Collaboration

Abstract: The outbreak of COVID‐19 in December 2019 required the formation of international consortia for a coordinated scientific effort to understand and combat the virus. In this Viewpoint Article, we discuss how the NMR community has gathered to investigate the genome and proteome of SARS‐CoV‐2 and tested them for binding to low‐molecular‐weight binders. External factors including extended lockdowns due to the global pandemic character of the viral infection triggered the transition from locally focused collaborativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In March 2020, the global consortium Covid19-NMR was formed. 26 It was its mission to make viral proteins and RNAs amenable to nuclear magnetic resonance (NMR) spectroscopic studies including protein and RNA preparation and the optimisation of sample conditions. RNA secondary structures were determined for all conserved RNA elements along with their NMR-based resonance assignment, thus providing a basis for investigations of the interaction of small molecules or viral and host proteins with the viral genome.…”
Section: Introductionmentioning
confidence: 99%
“…In March 2020, the global consortium Covid19-NMR was formed. 26 It was its mission to make viral proteins and RNAs amenable to nuclear magnetic resonance (NMR) spectroscopic studies including protein and RNA preparation and the optimisation of sample conditions. RNA secondary structures were determined for all conserved RNA elements along with their NMR-based resonance assignment, thus providing a basis for investigations of the interaction of small molecules or viral and host proteins with the viral genome.…”
Section: Introductionmentioning
confidence: 99%
“…Both strategies, while being effective, inevitably tend to be sensitive towards evolutionary pressure to evade the immune response or the antiviral agent. To provide a broader approach, our project Covid19-nmr (Duchardt-Ferner et al 2023), has focused on screening the entire proteome (Berg and Wirtz Martin and Altincekic et al 2022) and RNA genome of SCoV-2 to identify binding fragments for further medicinal chemistry campaigns. One underestimated but promising research area is the development of drugs targeting RNA, which could potentially revolutionize antiviral treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Within the global consortium Covid19-nmr ( 14 ), we have defined and investigated 15 individually folded RNA elements of the SARS-CoV-2 genome—located in the 5′-genomic end, the 3′-UTR and the frameshifting region—by nuclear magnetic resonance (NMR) spectroscopic studies and reported their secondary structures ( 15 ). These RNA elements have also been screened against small molecule libraries ( 16 ).…”
Section: Introductionmentioning
confidence: 99%